The Symbiotic Relationship Between the Virtual Computing Lab and Collaboration Technology - Dewan, Prasun; Junuzovic, Sasa; Sampathkumar, Govindaraj (ICVIC 2007, 2007)
The Virtual Computing Lab allows its users to remotely access computing resources spread-out across multiple sites. Collaboration technology allows users to work with each other from distributed sites. These two technologies have a symbiotic relationship wherein each potentially improves the capabilities of the other. Collaboration technology can be used to make users of the virtual computing lab aware of each others’ activities, thereby providing a sense of community and allowing sharing of research results. More subtle, collaboration technology can be used to create a shared environment that allows resource users and grantors to fluidly communicate with each other to ensure high and safe utilization of the resources. Even more subtle, the virtual computing lab can be used to conduct experiments that evaluate the scalability of various distributed collaboration architectures. Even more interesting, these three ways to integrate the two technologies can themselves be integrated.